A Review of Behavioral Observation Coding Approaches for the Trier Social Stress Test for Children - Thomassin, Kristel; Raftery-Helmer, Jacquelyn; Hersh, Jacqueline (Frontiers in Psychology, 2018)
The Trier Social Stress Test (TSST) has become one of the most widely-used protocols for inducing moderate psychosocial stress in laboratory settings. Observational coding has been used to measure a range of behavioral responses to the TSST including performance, reactions to the task, and markers of stress induced by the task, with clear advantages given increased objectivity of observational measurement over self-report measures. The current review systematically examined all TSST and TSST-related studies with children and adolescents published since the original work of Kirschbaum et al. (1993) to identify behavioral observation coding approaches for the TSST. The search resulted in 29 published articles, dissertations, and master’s theses with a wide range of coding approaches used. The take-home finding from the current review is that there is no standard way to code the Trier Social Stress Test for Children (TSST-C), which appears to stem from the uniqueness of investigators’ research questions and sample demographics. This lack of standardization prohibits conclusive comparisons between studies and samples. We discuss relevant implications and offer suggestions for future research.